Hydrogen Peroxide-Induced DNA Damage and Repair through the Differentiation of Human Adipose-Derived Mesenchymal Stem Cells. (10th October 2018) - Valverde, Mahara; Lozano-Salgado, Jonathan; Fortini, Paola; Rodriguez-Sastre, Maria Alexandra; Rojas, Emilio; Dogliotti, Eugenia
Abstract : Human adipose-derived mesenchymal stem cells (hADMSCs) are recognized as a potential tool in cell tissue therapy because of their capacity to proliferate and differentiate in vitro. Several studies have addressed their use in regenerative medicine; however, little is known regarding their response to DNA damage and in particular to the reactive oxygen species (ROS) that are present in the microenvironment of implantation. In this study, we used the ROS-inducing agent hydrogen peroxide to explore the responses of (1) hADMSCs and (2) derived terminally differentiated adipocytes to oxidatively generated DNA damage. Using single cell gel electrophoresis, a dose-related increase was found for both DNA breaks and oxidative lesions (formamidopyrimidine DNA glycosylase-sensitive sites) upon exposure of hADMSCs to hydrogen peroxide. DNA repair capacity of hADMSCs was affected in cells exposed to 150 and 200  μ M of hydrogen peroxide. An increase in the basal levels of DNA breaks and oxidative DNA lesions was observed through adipocyte differentiation. In addition, hydrogen peroxide-induced DNA damage increased through adipocyte differentiation; DNA repair capacity also decreased. This study is the first follow-up report on DNA repair capacity during adipogenic differentiation. Remarkably, in terminally differentiated adipocytes, DNA breakage repair is abolished while the repair of DNA oxidative lesions remains efficient.